The Charterhouse of Bruges - Jan van Eyck, Petrus Christus, and Jan Vos - Capron, Emma (The Frick Collection, 2018)
"At the heart of the exhibition is the reunion...for the first time in more than twenty years and the second time in their history...of the Exeter Madonna and the Frick Virgin, Jan Vos's two surviving commissions. Complementing them will be a selection of objects that place them in their rich context. Leaving questions of attribution aside, the exhibition will focus on the works' patronage, function, reception, and spiritual environment."
"This catalogue is published in conjunction with the exhibition The Charterhouse of Bruges: Jan Van Eyck, Petrus Christus, and Jan Vos on view at The Frick Collection from September 18, 2018, to January 13, 2019.". - Includes bibliography and index
Keywords: Eyck, Jan van -- 1390-1440; Christus, Petrus -- approximately 1410-1472 or 1473; Vos, Jan -- -1462 -- Art patronage -- Exhibitions; Elisabet -- Biblische Person; Eyck, Jan van -- 1390-1441; Vos, Jan -- 1612-1667; Barbara -- Heilige -- -306; Christus, Petrus -- 1410-1473; Frick Collection; Geschichte 1440-1450; Art patronage -- Belgium -- Bruges -- History -- 15th century -- Exhibitions; Painting, Flemish -- Belgium -- Bruges -- 15th century -- Exhibitions; Christian art and symbolism -- Belgium -- Bruges -- Medieval, 500-1500 -- Exhibitions; Kartause; Auftraggeber; Maria mit Kind; Motiv; Brügge; Ausstellungskatalog -- Frick Collection -- 18.09.2018-13.01.2019 -- New York, NY; Bildband